The benefits of both - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Mixed crop-livestock farming. A review of traditional technologies based on literature and field experiences FAO, 2001. 88 pp. ISBN 9251045763 US$ 14 Euro 13.60